1982
DOI: 10.1002/joc.3370020408
|View full text |Cite
|
Sign up to set email alerts
|

Cave climate: Assessment of airflow and ventilation

Abstract: Study of cave climates is a neglected aspect of microclimatology. An understanding of the processes that control cave climate is required in the study of cave flora and fauna, thermodynamic conditions for karst processes underground, hydrogeologic features of speleothems as well as human use of caves for recreational and commercial purposes. An understanding of cave airflow is of central importance as the climate of a cave is a function of air exchange with the outside environment. The study site is the Glowwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 3 publications
5
93
0
1
Order By: Relevance
“…Changes in pCO 2 production in the soil could be an addition to the observed seasonal pCO 2 pattern, but seem to be of minor importance compared to changes in cave ventilation at this tropical site. Similar conclusions have been made at numerous other sites ( De Freitas et al, 1982;Pflitsch & Piasecki, 2003;Spötl et al, 2005;Kowalczk & Froelich, 2010;Cowan et al, 2013;Gregorič et al, 2013). Mattey et al (2016) found that decay of organic matter washed down into the unsaturated zone appears to be a CO 2 source of similar importance, which is likely to be annually constant.…”
Section: Diurnal Variations In Temperature Andsupporting
confidence: 76%
“…Changes in pCO 2 production in the soil could be an addition to the observed seasonal pCO 2 pattern, but seem to be of minor importance compared to changes in cave ventilation at this tropical site. Similar conclusions have been made at numerous other sites ( De Freitas et al, 1982;Pflitsch & Piasecki, 2003;Spötl et al, 2005;Kowalczk & Froelich, 2010;Cowan et al, 2013;Gregorič et al, 2013). Mattey et al (2016) found that decay of organic matter washed down into the unsaturated zone appears to be a CO 2 source of similar importance, which is likely to be annually constant.…”
Section: Diurnal Variations In Temperature Andsupporting
confidence: 76%
“…The large amount of perennial ice in the Scarisoara Cave is a direct consequence of the cave's peculiar climate, which in turn is controlled by location and size of the cave entrance, the volume of the underground void, as well as local climatic conditions (Racovita and Onac, 2000). Scarisoara is a descending cave with a single entrance located at its upper part and therefore, belongs to the group of caves with seasonal bidirectional ventilation (Racovita 1967;De Freitas et al, 1982). This means, the aerodynamic exchanges with the exterior are limited to cold seasons when the outside colder and denser air sinks and cools down the cave.…”
Section: Location and Cave Descriptionmentioning
confidence: 99%
“…C. R. de Freitas and A. Schmekal Airflow in the cave has been studied in detail by de Freitas et al (1982) and shown to be the key component of a cave's climate (de Freitas & Littlejohn, 1987). The speed and direction of flow is determined by the difference of mean density of the outside and inside air (de Freitas et al, 1982). Since air density is mainly a function of air temperature, the latter can be used as the main indicator of airflow (de Freitas et al, 1982).…”
Section: Study Sitementioning
confidence: 99%
“…The speed and direction of flow is determined by the difference of mean density of the outside and inside air (de Freitas et al, 1982). Since air density is mainly a function of air temperature, the latter can be used as the main indicator of airflow (de Freitas et al, 1982). When the outside air is cooler and thus denser than the cave air, the warmer cave air rises and flows towards and then through the Upper Entrance and replaced by cold air at the Lower Entrance.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation